Influence of Predict Observe Explain (POE) Worksheet on Critical Thinking Ability on Impulse and Momentum - B. Anggit Wicaksono; I Dewa Putu Nyeneng; Wilda Verawati Simaibang (Jurnal Pembelajaran Fisika, 2021)
The study aims to determine the influence of the use of POE-based worksheets against the learners ' critical thinking ability on impulse and momentum material. This study was conducted in one of the state high schools in Bandarlampung, in the even semester of the school year, 2019/2020. The Research Population is all students of class X MIA. The design of this research uses the Non-Equivalent Pretest Posttest Control Group Design. This study uses a purposive sampling technique with X-grade samples MIA3 amounted to 36 learners as experimental classes and X-grade MIA4 numbered 36 students as control classes have relatively the same initial skills before the researcher performs the treatment. The results of the Independent sample T-Test show POE-based Worksheets on impulse and momentum material have a significant effect on learners ' critical thinking skills. Classes using the worksheets POE learning model showed higher critical thinking abilities with an average of N-Gain 0.70 versus a control class not exposed to the worksheets model Predict-Observe-Explaindengan N-Gain 0.60. This suggests that the use of POE-based worksheets in this research considerably influences learners ' critical thinking skills.Keywords: Critical thinking ability, Momentum impulse, Predict observe explain DOI: http://dx.doi.org/10.23960/jpf.v9.n1.202101